2018
DOI: 10.1177/1758573217750832
|View full text |Cite
|
Sign up to set email alerts
|

Augmented latissimus dorsi transfer: initial results in patients with massive irreparable posterosuperior rotator cuff tears

Abstract: Background: The surgical treatment of irreparable massive rotator cuff tears is challenging. The purpose of the present study was to report the initial outcomes after a modified latissimus dorsi transfer (LDT) augmented by acellular dermal allograft (ADA). Methods: This retrospective study includes 24 patients managed with LDT using ADA augmentation as a bursal-sided onlay between March 2009 and December 2015. Results: All patients were men with a mean age of 57 years (range 48 years to 70 years). Seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…They recommended performing an acromial osteotomy to limit disruption of the deltoid tendon and an augmentation repair using a collagen matrix. Sidler-Maier et al 32 presented preliminary outcomes using a bursal sideeonly dermal augmentation in patients with massive posterosuperior tears. At a mean follow-up of 27 months, patients reported significant improvements in forward flexion and all but 1 of the 24 patients reported being "satisfied" with their operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommended performing an acromial osteotomy to limit disruption of the deltoid tendon and an augmentation repair using a collagen matrix. Sidler-Maier et al 32 presented preliminary outcomes using a bursal sideeonly dermal augmentation in patients with massive posterosuperior tears. At a mean follow-up of 27 months, patients reported significant improvements in forward flexion and all but 1 of the 24 patients reported being "satisfied" with their operation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not find previous surgery, tendon retraction, or atrophy to have an effect on postoperative motion. 32 Although reverse total shoulder arthroplasty is a viable salvage procedure, implant longevity and failure preclude the use of arthroplasty in this young and active population. 33 Whereas latissimus dorsi tendon transfer is thought to restore external rotation and re-establish the anterior-posterior force couples on the humeral head, the orientation of the tenodesis places a nonphysiological vector across the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports emphasized therefore the use of an additional allograft tendon to cover and further reinforce the tendon suture interface. 21,22 This biomechanical study showed that the used 5-crossings stitching technique (Figure 4) provided a solid and strong tendon reinforcement, as tendon pull-out was only observed once as a failure mode.…”
Section: Discussionmentioning
confidence: 81%
“…1). There were 3 Level II studies, [52, 71, 87], 14 Level III studies [10, 18, 39, 42, 49, 50, 53, 55, 56, 62, 63, 65, 68, 76], and 69 Level IV studies [3, 4, 6, 8, 9, 11–13, 15–17, 19–33, 35, 37, 38, 41, 43, 45, 47, 48, 51, 54, 57–61, 64, 66, 67, 69, 72–75, 77–81, 84–86, 88–95]. The mean MINORS score was 18 for the 14 comparative studies and 8 for the 69 noncomparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 studies reported revision rates, with all 6 subgroups represented (Table 9). There were two studies in the allograft bridging/augmentation subgroup [62, 92], one study in the debridement subgroup [33], four studies in the repair subgroup [24, 52, 53, 74], eight studies in the SCR subgroup [6, 16, 42, 45, 48, 55, 58, 85], 6 studies in the spacer subgroup [17, 53, 54, 72, 75, 93], and 19 studies in the tendon transfer subgroup [9, 15, 20, 25, 27, 29, 30, 32, 37–39, 43, 49, 64, 70, 81, 87, 94, 95]. The overall revision rate of all studies was 7.4%.…”
Section: Resultsmentioning
confidence: 99%